2016
DOI: 10.1387/revpsicodidact.14300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of the Sexual Education Programme SOMOS on Sexual Experience and Attitudes of Adolescents Towards Sexuality // Evaluación de los efectos del Programa de Educación Sexual SOMOS sobre la experiencia sexual y las actitudes hacia la sexualidad de adolescentes

Abstract: The effects of the SOMOS Sexual Education Programme on attitudes towards sexuality in general and towards masturbation in particular, as well as the possible impact of that programme on the sexual experiences of pupils are studied. The investigation takes a sample of 123 adolescents enrolled in the 3rd year of Compulsory Secondary Education, aged between 13 and 17 years old. A design of repeated pre-test/post-test measurements was used with three experimental groups (71 students) and two control groups (52 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
12
0
4
Order By: Relevance
“…In addition, the results of an assessment regarding the effects of the SOMOS sex education program on the attitudes towards sexuality, in general, after interventional education, confirmed that the program fostered the development of positive attitudes towards sexuality while it significantly decreased negative attitudes towards masturbation. It was further found that the sexual experience of the students progressively increased regardless of the group they belonged to (26).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, the results of an assessment regarding the effects of the SOMOS sex education program on the attitudes towards sexuality, in general, after interventional education, confirmed that the program fostered the development of positive attitudes towards sexuality while it significantly decreased negative attitudes towards masturbation. It was further found that the sexual experience of the students progressively increased regardless of the group they belonged to (26).…”
Section: Resultsmentioning
confidence: 93%
“…Knowledge or Attitude of Women Most of the results reported the effect of sex education on increasing the women's knowledge. In addition, the results of some studies indicated that more progressive attitudes toward girls and women, less agreement with hegemonic masculinity ideology, and increases in sexual health, resource knowledge, and positive attitudes of the women (18,26,28,33) were effective in this respect. Adamczyk and Greif in their study found that gender empowerment was partially related to the relationship between education and HIV/AIDS knowledge (34).…”
Section: Discussionmentioning
confidence: 99%
“…Three of the quantitative studies were randomized controlled trials: Escribano et al ( 50 ), Pakarinen et al ( 51 ), and Ponsford et al ( 52 ), two applied cluster-randomized controlled designs: de Lijster et al ( 53 ) and Espada et al ( 60 ), and four applied a quasi-experimental design: Elliot et al ( 54 ), García-Vázquez et al ( 55 ), Zmyj and Wehlig ( 61 ), and Peters et al ( 62 ). Finally, four studies applied a descriptive design only reporting on post-intervention results: Alekseeva et al ( 56 ), Başar et al ( 57 ), Heras et al ( 58 ), and Pakarinen et al ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…Por el contrario, aquellos que tienen actitudes más erotofóbicas van a aceptar peor la sexualidad en cualquiera de sus manifestaciones, tendiendo a mostrar emociones desagradables por los estímulos sexuales, valorándolos negativamente, y experimentando mayor culpabilidad, evitación y ansiedad sexual ante las mismas (Zubeidat et al, 2003); así como menor nivel de conocimiento en cuanto a los riesgos que conllevan ciertas conductas sexuales y estar menos predispuestos al uso de métodos contraceptivos (Heras et al, 2016). De hecho, en un estudio ya clásico, se encontró que hombres erotofóbicos eran menos tendentes a utilizar condones que aquellos erotofílicos (Fisher, 1984; citado por Gómez-Zapiain, 1994).…”
Section: Introductionunclassified